Distribution of total phenols, flavonoids and hypericin in different plant organs of wild-growing St. John’s-wort (Hypericum perforatum L., Hypericaceae) from North Macedonia - Shabania, Arijeta; Karapandzova, Marija; Cvetkovikj Karanfilova, Ivana; Stefkov, Gjoshe; Simonoska Crcarevska, Maja; Kulevanova, Svetlana (Macedonian Pharmaceutical Association, 2019)
Hypericum perforatum L. (Hypericaceae) contains secondary metabolites that show noteworthy pharmacological activities. Therefore, the content of total phenols, flavonoids and hypericin from whole herb, flowers and leafs from St. John’s-wort collected over four consecutive seasons (2014-2017) from three different locations in western part of North Macedonia (Tetovo, Debar and Mavrovo) were investigated by three different spectrophotometric methods (using Folin-Ciocalteu reagent, NaNO2-AlCl3-NaOH and mixture of water/tetrahydrofuran). The quantity of total phenols obtained from different plant organs (leafs, whole herb and flowers) were 35.15-83.08 mg GAE/g, 55.41-98.52 mg GAE/g and 75.44-121.19 mg GAE/g, respectively. Afterword the total flavonoids contents were: 61.64-106.86 mg CE/g, 73.04-117.57 mg CE/g and 108.65-125.35 mg CE/g in leafs, whole herb and flowers, respectively, while the hypericin amounts were: 0.03-0.17 mg/g, 0.04-0.29 mg/g and 0.07-0.60 mg/g in leafs, whole herb, and flowers, respectively. Significant differences were observed in the quantities of total phenols, flavonoids and hypericin between the locations of harvesting, while the collection seasons were found not to be significant. Additionally, it can be seen that the flowers are characterized by higher amounts of total phenols, total flavonoids and hypericin compared to total herb and leaf in all three locations, therefore harvesting of St. John’s-wort should be made in a manner of obtaining larger quantities of flowers as harvesting material which could increase the bioactive compounds in the herbal row material. Keywords: Hypericum perforatum, plant organs, total phenols, flavonoids, hypericin, statistical analysis